Pre-equilibrium photons from the early stages of heavy-ion collisions - García-Montero, Oscar; Mazeliauskas, Aleksas; Plaschke, Philip; Schlichting, Sören (Journal of high energy physics, 2024)
We use QCD kinetic theory to compute photon production in the chemically equilibrating Quark-Gluon Plasma created in the early stages of high-energy heavy-ion collisions. We do a detailed comparison of pre-equilibrium photon rates to the thermal photon production. We show that the photon spectrum radiated from a hydrodynamic attractor evolution satisfies a simple scaling form in terms of the specific shear viscosity η/s and entropy density dS/dζ ∼ (Tτ1/3)3/2∞. We confirm the analytical predictions with numerical kinetic theory simulations. We use the extracted scaling function to compute the pre-equilibrium photon contribution in √s NN = 2.76 TeV 0–20% PbPb collisions. We demonstrate that our matching procedure allows for a smooth switching from pre-equilibrium kinetic to thermal hydrodynamic photon production. Finally, our publicly available implementation can be straightforwardly added to existing heavy ion models.
Gesehen am 12.08.2024